A Socio-Legal Study on Vaccine Tourism in the Context of Covid-19 Travel Restrictions - Mohammad Owais Farooqui; Shadi A. Alshdaifat; Mohd Imran Siddiquei (Emerging Science Journal, 2023)
The COVID-19 pandemic has affected the tourism industry harshly. The most effective way to steer clear of the virus is global vaccination. A novel concept of vaccine tourism arises from vaccine manufacturing corporations' limited stock and production capacity. The current paper aims to demystify the socio-legal and ethical underpinnings of vaccine tourism as well as analyze the restrictions on international travel imposed by major countries. The research critically examines key issues considering the literature's current arguments and integrates the current developments and challenges in the field of vaccine tourism. The paper addresses the fact that, in the current circumstances of travel restrictions, insufficiency of raw materials, ambiguous policies, vaccine passport authenticity, skewed distribution, and scarcity of vaccines around the world, the implementation of vaccine tourism is a big challenge. The study tries to understand the emerging concept of vaccine tourism and the major challenges to its growth. Vaccine tourism may be an instrument to revive the tourism sector post-COVID; therefore, understanding the current emerging issues around it would be significant for tourism literature. Doi: 10.28991/ESJ-2023-07-05-012 Full Text: PDF